Management of COVID-19 in Kidney Transplant Recipients: A Single-Center Case Series - Maruhum Bonar H. Marbun; Riahdo J. Saragih; Tantika Andina (International Journal of Nephrology)
Background. Kidney transplant recipients (KTRs) were reported to be at higher risk of developing severe coronavirus disease-2019 (COVID-19). Despite being one of the most impacted countries, little is known about KTRs with COVID-19 in Indonesia. This report aims to explore the management strategies and short-term clinical outcomes of KTRs with COVID-19 in an Indonesian transplant center. Methods. We observed KTRs who were admitted following COVID-19 diagnosis. Anamnesis, physical, laboratory, and radiologic examinations were performed. Demographic and transplant histories were recorded, along with symptoms, vaccination status, and management related to COVID-19. Results. Nineteen KTRs were observed and 14 (73.6%) were male. The most common presenting symptoms were fever, cough, and shortness of breath. Nine (47.3%) KTRs had severe-critical COVID-19. The mortality rate was 42.1%. Acute kidney injury (AKI) was present in six (31.6%) of KTRs, five (83.3%) of whom were nonsurvivors. The median D-dimer level was higher in nonsurvivors (5,800 versus 670 μL), while other laboratory parameters were comparable. Seven (36.8%) KTRs were vaccinated. The mortality rates of vaccinated and unvaccinated KTRs were 14.2% and 70%, respectively. Antiviral therapy, anticoagulant, intravenous immunoglobulin, and tocilizumab were prescribed to 89.5%, 89.5%, 15.8%, and 10.5%, respectively. Immunosuppressive therapy (IST) was halted in 68% of KTRs, among which 61.5% passed away. Conclusion. The clinical presentation of COVID-19 in KTRs was similar to that in the general population, whereas the mortality rate was higher. Management strategies for KTRs with COVID-19 should include prevention of AKI and hypercoagulation. Vaccination seems to be beneficial for KTRs, while temporary withdrawal of IST does not.